Wychowanki i uczennice w szkołach klasztornych w XVII i XVIII wieku - Szylar, Anna (Biuletyn Historii Wychowania, 2024)
Activities of monastic schools in the 17th and 18th centuries is a very interesting issue. The history of students and alumni of these schools deserves special attention. The article analyzes issues related to the recruitment to monastic schools, the social and territorial origin of students, the number of schoolgirls, the age at which they started education, staying in neophytes’ monastic schools and the further fate of the students. All these issues allow to broaden current knowledge about the upbringing of women in modern times. Archival source edits and studies have been used to write the article. A full list thereof has been supplied in the bibliography. This paper presents the most important issues concerning students of monastic schools.